Effect of water on impact strength for unsaturated polyester composites reinforced with E-glass fibers - Ghazi Hammed, Mohammed (Anbar Journal of Engineering Sciences, 2012)
The present research aimed to study the effect of distilled water on impact strength for unsaturated polyester composites reinforced with E-glass fibers with volume fraction 35%, all samples were prepared by using hand lay up technique. Unsaturated polyester resin was used as matrix for the reinforced materials that consist of artificial glass fibers (woven roving) with directional (0,90) and chopped glass fibers with the random direction. The samples were cutting with measurement (60 x 6) mm and the sample thickness dependent on the number of layers of glass fibers. The impact tests are carried out on samples under the influence of normal conditions (laboratory temperature). The results and examinations for these samples shows acceptable improvement in impact strengths of the matrix was observed after addition of glass fibers, to explain the effect of water on impact properties, the samples immersion in water for (50) days. The results show that as the exposure time increased the impact strength of samples increase.